Financing the digitalisation of small and medium-sized enterprises The enabling role of digital innovation hubs - Casorat, Alberto (2020)
The study provides an overview of the role of digital innovation hubs and snapshot of the status of digitalisation in Europe. It comes in a very timely moment. The current COVID-19 crisis has highlighted even more the importance of digitalisation. Small and medium-sized enterprises (SMEs) are at the centre of the economic crisis brought on by the COVID-19 pandemic and containment measures, more now than during the 2008 financial crisis. This has clearly shown the importance and the need to accelerate the digital transformation to make businesses more resilient and agile. The study reviews access-to-finance conditions for the digitalisation of SMEs and the role of digital innovation hubs as key enablers in the wider ecosystem. It highlights how the propensity to digitalisation and digital maturity of SMEs is not only affected by financial factors (access to finance) but also by non-financial factors (knowledge and ambition to digitalise). In particular, the study shows the crucial role of digital innovation hubs and the wider eco-system in supporting the digitalisation of SMEs. Many digital innovation hubs have taken rapid actions to respond to the COVID-19 crisis and better help SMEs in the current circumstances. The study was carried out by InnovFin Advisory in collaboration with the European Investment Advisory Hub, with the support of Gartner.